The Post-Screen Through Virtual Reality, Holograms and Light Projections Where Screen Boundaries Lie - Ng, Jenna (MediaMatters, 2021)
Screens are ubiquitous today. They display information; present image worlds; are portable; connect to mobile networks; mesmerize. However, contemporary screen media also seek to eliminate the presence of the screen and the visibilities of its boundaries. As what is image becomes increasingly indistinguishable against the viewer's actual surroundings, this unsettling prompts re-examination about not only what is the screen, but also how the screen demarcates and what it stands for in relation to our understanding of our realities in, outside and against images. Through case studies drawn from three media technologies - Virtual Reality; holograms; and light projections - this book develops new theories of the surfaces on and spaces in which images are displayed today, interrogating critical lines between art and life; virtuality and actuality; truth and lies. What we have today is not just the contestation of the real against illusion or the unreal, but the disappearance itself of difference and a gluttony of the unreal which both connect up to current politics of distorted truth values and corrupted terms of information. The Post-Screen Through Virtual Reality, Holograms and Light Projections: Where Screen Boundaries Lie is thus about not only where the image's borders and demarcations are established, but also the screen boundary as the instrumentation of today's intense virtualizations that do not tell the truth. In all this, a new imagination for images emerges, with a new space for cultures of presence and absence, definitions of object and representation, and understandings of dis- and re-placement - the post-screen.